Gender Equality and Discrimination among Junior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Safety inside educational institutions is one of the topmost priorities of every administrators. This includes ensuring that there is a positive environment for gender and development. While egalitarian treatment of people regardless of gender is becoming a trend in the school policies, prevalence of gender-based discrimination is almost inevitable. Thus, the researchers explored the prevalence of gender-based impartiality and discrimination among the respondents. The study utilized quantitative descriptive design, surveying 104 Junior High School students enrolled at Union Christian College. The researchers used adapted survey questionnaire. The data was analyzed using weighted mean to describe the status of gender equality and discrimination, t-test to determine comparisons in the variable when grouped according to sex, while analysis of variance was used for comparing groups according to sexual preference. The results revealed that the respondents perceive fairness, equity, and impartial treatment between genders in their experiences or surroundings, stating that their right to express themselves are respected, and that their peers respect them for their gender identity. Meanwhile, there is a tendency for the respondents to associate themselves with those who have the same gender identity as theirs, and avoid those who hurt people just for having different gender identity. There is no significant difference in their perceptions when grouped according to sex, but significant comparisons exist when grouped according to sexual preference. The researchers recommend that school policies strenghten egalitarian gender and development practices to make the environment more inclusive for all genders. Advocacy plans to elevate gender expression are also encouraged. Future studies may be conducted on the orientedness of school polices to GAD.
Keywords: school polices; gender and development; gender-based discrimination